Association between inflammatory burden index and prognosis in patients with coronary heart disease: A retrospective study. - Wen Lu; Xiaoqin Liao; Yan Jiang; Baolin Luo; Liangwan Chen; Yanjuan Lin (PLoS ONE, 2025)
Background Increasing evidences indicate that systemic inflammation plays a significant role of adverse prognosis in patients with coronary heart disease (CHD). The inflammatory burden index (IBI) is a novel biomarker that reflects systemic inflammation. The aim of this study was to investigate the association between IBI and prognosis of CHD patients. Methods In this retrospective analysis, data from 2453 CHD patients enrolled from December 2017 to December 2022.IBI was defined as neutrophil/lymphocyte*C-reactive protein, with patients categorized into four groups based on quartiles of baseline IBI levels. The primary outcome was adverse cardiovascular and cerebrovascular events (MACCEs) occurring during hospitalization, which included repeat revascularization, new-onset atrial fibrillation (NOAF), stroke, and all-cause in-hospital mortality. Multivariate logistic regression models and restricted cubic spline (RCS) analysis were used to investigate the association between IBI and prognosis of CHD patients. Results High levels of IBI were associated with higher risk of MACCEs, especially when IBI ≥ 45.68, patients exhibited a higher risk of MACCEs (P < 0.05). After adjusting for baseline confounders, multivariate logistic regression analysis demonstrated that baseline IBI was an independent predictor for NOAF (Odds Ratio (OR): 2.05; 95% confidence interval (CI): 1.30-3.24; P = 0.002) and contrast-induced nephropathy (CIN) (OR: 1.95; 95%CI: 1.16-3.28; P = 0.012) in CHD patients, mainly driven by the highest quartile. In addition, RCS confirmed a linear relationship between IBI and NOAF (P for non-linear = 0.425) and a nonlinear relationship with CIN (P for non-linear = 0.032). Conclusion IBI is a promising biomarker of systemic inflammation in CHD patients, where higher IBI levels are associated with adverse prognosis. These findings may aid clinicians in precise decision-making to improve outcomes in patients with CHD.